2015
DOI: 10.1088/0022-3727/48/43/432001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the spatial electron density distribution of EUV-induced plasmas

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 28 publications
6
28
0
Order By: Relevance
“…where e and m e are the charge and mass of an electron, respectively, and ε 0 is the permittivity of vacuum. In practice, MCRS has been applied to EUV-induced plasmas by sending a pulsed EUV beam through a cavity that contained holes in its top and bottom cavity lids for this purpose (see Figure 5) [11,17,18,34,35,50]. Microwave (MW) antennas that are inserted through the cavity wall are used to send in microwave radiation and to record the cavity's response (either in transmission or reflection mode).…”
Section: Microwave Cavity Resonance Spectroscopy (Mcrs)mentioning
confidence: 99%
“…where e and m e are the charge and mass of an electron, respectively, and ε 0 is the permittivity of vacuum. In practice, MCRS has been applied to EUV-induced plasmas by sending a pulsed EUV beam through a cavity that contained holes in its top and bottom cavity lids for this purpose (see Figure 5) [11,17,18,34,35,50]. Microwave (MW) antennas that are inserted through the cavity wall are used to send in microwave radiation and to record the cavity's response (either in transmission or reflection mode).…”
Section: Microwave Cavity Resonance Spectroscopy (Mcrs)mentioning
confidence: 99%
“…[8][9][10] The density and the dynamics of one of the dominant plasma species in these plasmas, i.e., the electrons, have been investigated numerically 11,12 and experimentally by means of Langmuir probes 13 and temporally resolved Microwave Cavity Resonance Spectroscopy (MCRS) in low pressure argon [14][15][16] and hydrogen 16,17 environments. Double-mode MCRS 18 and multi-mode MCRS 19 have revealed this information on spatially resolved, while the combination of MCRS measurements and an ambipolar diffusion model showed that in the moderately high pressure regime (>3 Pa in argon 20 and >6 Pa in hydrogen 3 ), electrons thermalize to values close to room temperature in the temporal afterglow of these pulsed plasmas. 20 Especially of interest when studying the interaction of EUV-induced plasmas with plasma-facing surfaces are the total ion flux and the ion energy distribution functions (IEDFs) of the ionic compounds impinging upon the surface.…”
mentioning
confidence: 92%
“…e simulated evolution of the effective volume is non monotonic in time. A similar effect was observed in experiments via the ratio of the electron densities measured using 010 and 110 cavity modes [121]. However, in simulations, the decrease of the effective volume just aer the EUV pulse is caused by the convolution of the plasma density with the spatial profile of the microwave mode in the cavity.…”
Section: Relation Of Field Averaged Electron Density and Simulated Vasupporting
confidence: 75%